EFIKASI SUPLEMENTASI FORMULA TEMPE BENGKUANG TERHADAP KADAR ALBUMIN DAN Z-SKOR BERAT BADAN MENURUT UMUR (BB/U) PADA ANAK GIZI KURANG - Symond, Denas; Oenzil, Fadil; Darwin, Eriyati; Lipoeto, Nur Indrawati (Jurnal Gizi dan Pangan, 2016)
The aim of this study was to determine the efficacy of formulated tempe-yam supplementation on weight for age z-score of underweight children aged 2-4 years. A quasi experiment pre-post test with control group design was applied in this study for four weeks. The intervention group consist of 19 children given formulated tempe-yam 100 g/d; and the control group consist of 19 children given biscuit 100 g/d in Padang Pariaman district, West Sumatera. Data collected included weight, height, and albumin level. Paired t-test was applied for the data analysis. The results of this study found significant differences in albumin level before and after on control group (p<0.05). Then, the results of this study also found significant differences in weight for age z-score before and after on intervention group (p<0.05). Therefore, formulated tempe-yam supplementation as food sumplementation need to be considered for underweight children.Keywords: albumin level, food suplementation, tempe-yam, weight-for age z-score